RANCANG BANGUN APLIKASI BENGKEL MOTOR BERBASIS ANDROID DI KOTA MAKASAR - Thias Angela Desan; Hamdan Arfandy; Baizul Zaman (STMIK KHARISMA Makassar, 2020)
Now all the desired information can be obtained using mobile phone/ mobile media. This is due to the function of the mobile phone which has a small size and easily to carry will make it easy for users to find the desired information quickly and easily. One problem that is often happened is that motorcyclists facing on the road are tire bans, damage that motorcyclists themselves don't aware and the difficulty of finding the nearest motorcycle repair shop. In order to solve the problem that happened to the motorcyclists, the author tries to make a motorcycle repair shop application to provide information on the location of the workshop. Based on these problems so research is conducted to develop an application that will display the location of motorcycle repair shops with information on workshop names, telephone numbers, opening days and hours of closure, with these applications it is expected that users can find out the location of motorcycle repair shops to make it more precise and save time by means of mobile